Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Hierarchical tubular carbon with differentiated Co/N/P functional units for selective silver recovery via capacitive electrosorption-reduction coupling - Linyi Ren; Yongping He; Fen Li; Lei Zhang; Ao Qiu; Xiayu Li; Xinhua Huang (Desalination, 2026)

A competitive binding strategy to fabricate silk fibroin/PANI hydrogels for integrated self-powered flexible supercapacitors and strain sensors - Chengzhao Liu; Yuanhang Luo; Xinyi Zhang; Fen Zhu; Yulan Liu; Huabo Huang; Xianghua Yu; Jiayou Ji; Liang Li (Chemical Engineering Journal, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Corrigendum to “Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide” [Food Res. Int. 230 (2026) 118574] - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying Li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

Urban Cooling Island Dynamics During the Development of an Ecological Urban Agglomeration in China - Ziwu Pan; Zunyi Xie; Lifei Huang; Fen Qin; Minmin Yu; Shuyu Yang; Zihan Wang; Jinyuan Han; Zenyan Wang; Yanping Cao; Zhihua Shi; Cangyu Li (Chinese Geographical Science, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Phosphorus Speciation and Mobility in the Dredged Sediment of an Urban Lake: The Role of Coupled Fe-S-P Dynamics and Microbial Succession - Baoquan Li; Min Zhang; Jicheng Zhong; Jiayu Qin; Haiyuan Cai; Chuanzhe Sun; Fanyan Yang; Yanjun Wu; Shanshan Liu; Hui Yang; Fen Huang (Water Research, 2026)

Unconventional seasonal variation and mechanisms of sediment phosphorus release in an Urban lake - Baoquan Li; Suisui Zhang; Yanjun Wu; Ying Li; Min Zhang; Chuanzhe Sun; Fanyan Yang; Yuyi Wang; Shanshan Liu; Hui Yang; Fen Huang; Jicheng Zhong (Journal of Environmental Sciences, 2026)

Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

Front-face synchronous fluorescence spectroscopy coupled with PLSR for rapid quantitative analysis of Chinese five-spice powder composition - Fei-Yue Chen; Li-Fen Zhang; Hong-Yan Pan; Xia Huang; Pei Yi; Zhi Jin; Peng-Hui Zhu; Jin Tan (Food Research International, 2026)

Sensitivity Analysis of a SAR Model for Microseismic Monitoring in the Three Gorges Reservoir Area - Xiao-tong Shen; Li-fen Zhang; Jing-gang Li; Yan-nan Zhao; Sheng-qi Dai; Jing-xuan Huang (Applied Geophysics, 2026)

A Network Information-Based Behavior Change Wheel for Populations at High Risk of Developing Gastric Cancer - Wen-Lei Huang; Shi-Guang Ren; Le-Jian He; Fen Xie; Hui-Lan Zhai; Dan-Dan Wang; Lu Jiang; Xue-Qin Li (Journal of Cancer Education, 2026)

NaCl and light quality reprogram carbohydrate metabolism to modulate growth, quality, and flavor in mustard (Brassica juncea) sprouts - Hongmei Di; Ling Li; Liping Su; Lisha Peng; Ling Rao; Zhifeng Chen; Victor Hugo Escalona; Jing Yang; Yu'nong Zhou; Yong Li; Xuena Yu; Kehao Liang; et al. (Food Chemistry, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

The bactericidal efficacy of carvacrol against drug-resistant Streptococcus iniae and its protective effects on channel catfish (Ictalurus punctatus) - Lizi Yin; Minmin Wang; Jianing Wu; Xiaonan Li; Fen Chen; Bowen Liu; Yi Geng; Xiaoli Huang; Defang Chen; Ping Ouyang (Aquaculture, 2026)

Motor Cortex VIP Interneurons Participate in Dexmedetomidine-Associated Sleep Modulation - Wei Wang; Hanmei Zhang; Tianqi Zhang; Qianyi Huang; Jiaxin Li; Nuo Li; Yue Xi; Xiaohan Yang; Fen Wang; Jun Tu; Dongmei Ji; Juan Cheng (Molecular Neurobiology, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

Structure-driven transparent and self-healing polyimides for durable flexible low-E window films - Fen Zhao; Xiwei Mo; Yulin Li; Yunkang Luo; Jianqiao Zhao; Zhaoshi Yu; Heng Xu; Hao Huang; Bin Hu; Guoli Tu (Chemical Engineering Journal, 2025)

Association between legume consumption and risk of esophageal cancer among Chinese adults: a 17-year prospective cohort study - Fengyi Huang; Xiaorui Zhang; Jiayue Li; Xinqing Li; Ru Chen; Shaoming Wang; Fen Liu; Wenqiang Wei (Cancer Causes & Control, 2025)

Assessing Spatiotemporal Characteristics, Health Impacts and Related Economic Losses of PM2.5, PM10 and O3 in Beijing-Tianjin-Hebei Region from 2015 to 2020 - Ran Gao; Qin Li; Yanping Zhang; Fei Che; Xiaorui Zhang; Yijie Wang; Yijun Zhang; Xite Zheng; Quanmei Li; Fengyi Huang; Chuning Luo; Wanqi Liu; et al. (Environment, Development and Sustainability, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

The role of N6-methyladenosine (m6A) modification in plants - Cui-Xian Qin; Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Miao Wang; You-Qiang Pan; Li Zhou; Bao-Qing Zhang; Jian-Hui Zhou; Dong-Liang Huang (Theoretical and Applied Genetics, 2025)

Effect of Dandelion Root Extract on Growth, Biochemical Indices, Antioxidant Capacity, Intestinal Histomorphology and Microbiota in Micropterus salmoides - Peng-Ao Liu; Hong-Ling Yang; Jian Huang; Fen Li; Ke-Yun Huang; Zi-Xin Liu; Guo-He Cai; Yun-Zhang Sun (Fishes, 2025)
Intensive aquaculture systems face challenges including compromised immune function and hepatointestinal damage in cultured species. Therefore, it is urgent to seek effective feed additives to strengthen health and immunity in intensive aquaculture. This study evaluated the potential of dandelion root extract (DRE) for improving growth performance, immune response, and hepatointestinal health in juvenile largemouth bass (Micropterus salmoides). Fish were fed diets supplemented with 0.05% (DRE1), 0.1% (DRE2), and 0.15% (DRE3) DRE for 42 days. The results showed that DRE supplementation had no significant effect on growth performance indicators (p > 0.05). However, compared to the control group, the DRE2 and DRE3 groups exhibited significantly reduced AST and ALT activities (p

Quantitative assessment of trophic flow based on polyunsaturated fatty acids reveals that high‐quality algae support aquatic food webs irrespective of dams - Juan Huang; Fen Guo; Martin J. Kainz; Stuart E. Bunn; Xiaoguang Ouyang; Feilong Li; Qingping Du; Yuan Zhang (Limnology and Oceanography, 2025)
High‐quality, yet less abundant, food sources sustain river food webs. However, the impacts of dams on these sources and their nutritional contributions to aquatic animals are not well understood. A substantial knowledge gap exists in understanding the quantitative contribution of basal food sources, such as periphyton, to aquatic animal diets and their role in supporting aquatic animals. This study fills this gap by using long‐chain polyunsaturated fatty acids as biomarkers to quantify the dietary contributions of periphyton, submerged leaves, and macrophytes to macroinvertebrates and fish in dammed rivers. Our results showed that periphyton contributed more to the lipid diets of macroinvertebrates and fish than submerged leaves and macrophytes, regardless of dams, and was a high‐quality food source supporting aquatic food webs. The dietary contribution of periphyton to macroinvertebrates decreased at the downstream sites of small dams compared to the upstream sites, while the contribution of leaves and macrophytes increased due to dam‐induced changes in periphyton nutritional quality. The nutritional quality of periphyton correlated positively with its contribution to invertebrate grazers and filterers, while its contribution to fish varied depending on the feeding strategies of fish species. Our findings underscore periphyton as a high‐quality dietary source in dammed river ecosystems and suggest that improving its nutritional quality enhances its contribution to the lipid diets of macroinvertebrates and fish.

Baicalin reduced vandetanib induced myocardial injury by regulating redox balance and NLRP3 inflammasome pathway - Fen Wang; Jianwei Li; Zhixuan Zhang; Guangyi Huang; Xiaodong Zhang; Qian Liu; Wang Xiao; Fengqi Liu; Jialong Sun; Yankui Liu; Yiyi Ma; Ruijuan Zhuang; et al. (Tissue and Cell, 2025)

Discovery of phenoxazine congeners as novel α-glucosidase inhibitors and identification of their biosynthetic gene cluster from Streptomyces sp. CB00316 - Lin Jiang; Pingzhi Huang; Aijie Li; Bin Fen; Yani Zhong; Caijun Tang; Guangling Wu; Wenlei Wang; Yuhan Chen; Jian Pan; Genyun Tang; Hong Pu (Archives of Microbiology, 2025)

Evaluation of the antibacterial activity and mechanism of cannabigerol against drug-resistant Streptococcus iniae in vitro - Jianing Wu; Minmin Wang; Tingke He; Xiaonan Li; Bowen Liu; Fen Chen; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Ping Ouyang (Archives of Microbiology, 2025)

Experimental and numerical study on the hydrodynamic characteristics of a cube fish cage integrated into a wind turbine jacket foundation - Yuan-Mao Zhang; Fen-Fang Zhao; Liu-Yi Huang; Huan-Ran Li; Chun-Wei Bi (Ocean Engineering, 2025)

Dynamic proteome and acetylome profiling reveals key regulators of sucrose accumulation in sugarcane - Miao Wang; Ao-Mei Li; Zhong-Liang Chen; Cui-Xian Qin; Fen Liao; You-Qiang Pan; Prakash Lakshmanan; Xiao-Feng Li; Dong-Liang Huang (Plant Cell Reports, 2025)

Glutathione-s-transferase regulates oxidative stress in Megalurothrips usitatus in response to environmental stress - Wenbo Dong; Youxing Zou; Chenyang Zhao; Tianbao Huang; Wayne Jiang; Fen Li; Shaoying Wu (Pesticide Biochemistry and Physiology, 2025)

Plant venation-inspired bio-based adhesive with toughness, wide temperature adaptability, and long-term adhesion - Dongna Li; Xiaoge Ye; Zhen Li; Shiyao Huang; Rong Zhao; Xiaojun Ma; Jianing Li; Fen Yin (Chemical Engineering Journal, 2025)

Enhanced biodegradation of glyphosate by Chlorella sorokiniana engineered with exogenous purple acid phosphatase - Si-Fen Liu; Zhong-Chen Yi; Zi-Qiong Huang; Zhen-Dong Yuan; Yu-Cheng Yang; Yongteng Zhao; Qing-Yu He; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Water Research, 2025)

Species-specific sensitivity to CuO nanoparticles: Establishing seawater quality criteria for Chinese marine ecosystems - De-chi Lu; Qing-Wei Li; Xin-Ming Pu; Heng Zhang; Lei Huang; Zhenguang Yan; Jin-Fen Pan (Science of The Total Environment, 2024)

In vitro gastrointestinal digestion and fecal fermentation behaviors of pectin from feijoa (Acca sellowiana) peel and its impact on gut microbiota - Zuoyi Zhu; Xinyue Song; Jiarong Yao; Zhen Li; Zhongping Huang; Huijun Liu; Wei Liu; Fen Dai (Food Research International, 2024)

Soil eDNA biomonitoring reveals changes in multitrophic biodiversity and ecological health of agroecosystems - Kaihang Xing; Weijun Lu; Qiqi Huang; Jingze Wu; Heping Shang; Qian Wang; Fen Guo; Qingping Du; Zhonglong Yin; Yuan Zhang; Feilong Li (Environmental Research, 2024)

Independent and interactive effects of particulate matter and meteorological factors on hand, foot and mouth disease in Fuyang - Wanwan Ma; Wenbin Shen; Lei Gong; Yongkang Xiao; Sai Hou; Liang Sun; Huaibiao Li; Fen Huang; Jiabing Wu (International Journal of Biometeorology, 2024)

Acylated anthocyanins from Dendrobium officinale Kimura & Migo: Structural characteristics, antioxidant and hypoglycemic activities - Zuoyi Zhu; Xinyue Song; Yali Huang; Yunzhu Jiang; Jiarong Yao; Zhen Li; Zhongping Huang; Fen Dai (Food Chemistry, 2024)

The Ecological Niches and Interspecific Associations of the Dominant Fishes in the Xiamen Seas, China - Liang-Min Huang; Hao-Qi Xu; Jia-Yue Yu; Yong-He Chen; Jia-Qiao Wang; Fen-Fen Ji; Jun Li; Jian-Di Cai; Ta-Jen Chu (Fishes, 2024)
Fish are vital in enhancing the stability of marine ecosystems. Therefore, understanding the ecological niches and interspecific correlation characteristics of their dominant species provides a good scientific basis for the protection and management of marine biodiversity. In this study, on the basis of survey data from trawls conducted in the waters off Xiamen in the spring (April) and autumn (November) of 2021, the ecotopes and interspecies connectivity of the dominant fish species were investigated using the relative importance index (IRI), χ2 tests, the association coefficient (AC), and Pearson and Spearman analyses. According to the IRI, there were 23 fish species with higher values, including 15 species in spring and 15 species in autumn. The 15 dominant fish species could be subdivided into wide-, medium-, and narrow-ecotope species, of which there were 2 and 3 wide-ecotope types in spring and autumn. The niche overlap indices exhibited a range of 0.000–0.809 in the spring and 0.000–0.915 in the autumn, showing small differences between the two seasons. The interspecific correlations between the dominant fishes in Xiamen’s waters in spring and autumn were weak, and both showed non-significant positive correlations, indicating that the correlations between the dominant fishes in this sea area are relatively independent. The findings of this investigation provide a fundamental database and theoretical framework for researching the adaptive mechanisms of marine fish in the Xiamen Seas.

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Ucf-101 alleviates Ischaemia/Reperfusion induced retinal inflammation and injury via suppressing oxidative damage - Yuan-Jun Qin; Guangyi Huang; Jing Liao; Li Jiang; Fen Tang; Ningning Tang; Yiyi Hong; Chaolan Shen; Qianqian Lan; Fan Xu; Lifei Chen (Journal of Molecular Histology, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

Response of weathering carbon sink effect to anthropogenic sulfuric acid in different lithological catchments: A case study from Southwest China - Yincai Xie; Peng Qian; Jun Li; Shi Yu; Xiongyi Miao; Yongli Guo; Fen Huang; Qiong Xiao; Liankai Zhang (Journal of Asian Earth Sciences, 2024)

Amplifying enantioselectivity in asymmetric transformations using heterogeneous chiral single-rhodium-site catalyst with sustained catalytic activity - Junwen Wang; Feng Liang; Junrong Huang; Jun Li; Jingyuan Liao; Chengyao Zhao; Hengzhi You; Tao Tu; Fen-Er Chen (Chemical Engineering Journal, 2024)

Individual and combined treatments of 2,4-epibrassinolide (EBR) and calcium chloride (CaCl2) maintain the postharvest quality of baby mustard - Hongmei Di; Ruobin Liu; Yutong Zhang; Zhifeng Chen; Jie Ma; Victor Hugo Escalona; Duchen Liu; Huanhuan Huang; Zhi Huang; Yi Tang; Huanxiu Li; Bo Sun; et al. (Postharvest Biology and Technology, 2024)

Sugarcane borers: species, distribution, damage and management options - Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Yong Zhao; Cui-Xian Qin; Miao Wang; You-Qiang Pan; Shao-Long Wei; Dong-Liang Huang (Journal of Pest Science, 2024)
Lepidopteran borers stand out as the most destructive pests in sugarcane, leading to reductions in stalk weight, juice quality and sugar recovery. Presently, integrated pest management (IPM) systems are utilized for sugarcane borer management, employing diverse methods encompassing cropping system, chemical pesticides, behavioral manipulation, biological agents and the selection of resistant varieties. However, the effectiveness of this strategy remains controversial due to concerns about harmful residues, formulation limitations, environmental variability, labor shortages and increased input costs. Currently, multiple lines of transgenic sugarcane expressing insecticidal genes from the bacterium Bacillus thuringiensis (Bt) have been developed globally, offering the prospect of increases production with reduced pesticides application, thereby eliminating the negative effect of IPM. In Brazil, the first genetically modified sugarcane cultivars resistant to the sugarcane borer have been approved and released for commercial cultivation, shedding a bright light on a viable solution for sugarcane borers. This paper reviews borer species and distribution, the significant damage caused by sugarcane borers, current control approaches and the future effective control strategies. Additionally, this work provides comprehensive understanding on Bt sugarcane, serving as an additional tool to complement conventional sugarcane borers control resistance programs.

Determination of the Elemental Iodine in Human Breast Milk by Inductively Coupled Plasma mass Spectrometry - Chun-Jui Huang; Jia-Zhen Li; Chii-Min Hwu; Harn-Shen Chen; Chang-Ching Yeh; Fan-Fen Wang; Chen-Chang Yang (Biological Trace Element Research, 2024)

Tsaokoflavanols A1–J1: Flavanol-fatty alcohol hybrids with HPL inhibitory activity from Amomum tsao-ko - Tian-Rong Yang; Shi-Chao Huang; Yun-Fen Wang; Zai-Xiang Lou; Shao-Xing Dai; Li-Hua Su; Min Xu (Phytochemistry, 2024)

How do small dams alter river food webs? A food quality perspective along the aquatic food web continuum - Juan Huang; Fen Guo; Michele A. Burford; Martin Kainz; Feilong Li; Wei Gao; Xiaoguang Ouyang; Yuan Zhang (Journal of Environmental Management, 2024)

Geochemical mechanisms of water/CO2-rock interactions in EGS and its impacts on reservoir properties: A review - Binbin Gao; Yiman Li; Zhonghe Pang; Tianming Huang; Yanlong Kong; Bin Li; Fen Zhang (Geothermics, 2024)

Assessing the impact of river connectivity on fish biodiversity in the Yangtze River Basin using a multi-index evaluation framework - Aopu Li; Juntao Fan; Fen Guo; Luke Carpenter-Bundhoo; Guoxian Huang; Yue Shi; Yuyin Ao; Jingfu Wang (Environmental Research, 2024)

Effect of exposures to multiple metals on blood pressure and hypertension in the elderly: a community-based study - Wen-lei Hu; Wei Xiao; Wen-bin Shen; Yue-yang Wu; Xue Li; Qi Zhong; Guo-ao Li; Huan-huan Lu; Jian-jun Liu; Zhi-hua Zhang; Fen Huang (BioMetals, 2024)

The effect of the design of the mini cyclonic DPIs on the emitted dose by modelling approach - Zeyu Li; Zhenbo Tong; Lixing Zhang; Fen Huang; Aibing Yu (Journal of Aerosol Science, 2024)

Assessment of the impact of dams on aquatic food webs using stable isotopes: Current progress and future challenges - Fen Guo; Brian Fry; Keheng Yan; Juan Huang; Qian Zhao; Kaitlyn O'Mara; Feilong Li; Wei Gao; Martin J. Kainz; Michael T. Brett; Stuart E. Bunn; Yuan Zhang (Science of The Total Environment, 2023)

Geochemical behaviors of rare earth elements in granite-hosted geothermal systems in SE China - Fen Zhang; Yiman Li; Xiaocheng Zhou; Tianming Huang; Jiao Tian; Yuanzhi Cheng; Yajing Zhao (Geothermics, 2023)

Structural characteristics, functional properties, antioxidant and hypoglycemic activities of pectins from feijoa (Acca sellowiana) peel - Zuoyi Zhu; Xinyue Song; Jiarong Yao; Zhen Li; Yunzhu Jiang; Qing Yu; Zhongping Huang; Huijun Liu; Yingping Xiao; Fen Dai (Food Chemistry, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Dose-response formation of N7-(3-benzo[1,3]dioxol-5-yl-2-hydroxypropyl)guanine in liver and urine correlates with micronucleated reticulocyte frequencies in mice administered safrole oxide - Kuen-Yuh Wu; Yu-Tzu Wei; Yu-Syuan Luo; Li-Chin Shen; Bao-Suei Chang; Ya-Yin Chen; Yan-Chi Huang; Hui-Fen Huang; Wen-Sheng Chung; Su-Yin Chiang (Food and Chemical Toxicology, 2023)

The combined effects of exposure to multiple PM2.5 components on overweight and obesity in middle-aged and older adults: a nationwide cohort study from 125 cities in China - Xue Li; Yueyang Wu; Guoao Li; Wenbin Shen; Wei Xiao; Jianjun Liu; Wenlei Hu; Huanhuan Lu; Fen Huang (Environmental Geochemistry and Health, 2023)

The impact of multiple metals exposure on the risk of developing proliferative diabetic retinopathy in Anhui, China: a case–control study - Yan-Qing Li; Si-Tian Zhang; Nai-Yu Ke; Yan-Cheng Fang; Wen-Lei Hu; Guo-Ao Li; Fen Huang; Yan-Feng Zhou (Environmental Science and Pollution Research, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

The impact of ambient air pollutants on childhood respiratory system disease and the resulting disease burden: a time-series study - Wenbin Shen; Xue Li; Qingfeng Fang; Guoao Li; Wei Xiao; Yueyang Wu; Jianjun Liu; Wenlei Hu; Huanhuan Lu; Fen Huang (International Archives of Occupational and Environmental Health, 2023)

An efficient LSTM network for predicting the tailing and multi-peaked breakthrough curves - Jie Niu; Shan Li; Wei Xu; Feifei Dong; Fen Huang; Han Qiu (Journal of Hydrology, 2023)

CRISPR/Cas9-mediated BoaAOP2s editing alters aliphatic glucosinolate side-chain metabolic flux and increases the glucoraphanin content in Chinese kale - Hao Zheng; Wenli Huang; Xiangxiang Li; Huanhuan Huang; Qiao Yuan; Ruobin Liu; Hongmei Di; Sha Liang; Mengyu Wang; Mengyao Li; Zhi Huang; Yi Tang; et al. (Food Research International, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Metagenomic evidence for antibiotics-driven co-evolution of microbial community, resistome and mobilome in hospital sewage - Jiayu Sun; Yumeng Yuan; Leshan Cai; Mi Zeng; Xin Li; Fen Yao; Weidong Chen; Yuanchun Huang; Muhammad Shafiq; Qingdong Xie; Qiaoxin Zhang; Naikei Wong; et al. (Environmental Pollution, 2023)

Correlations between flavor and glucosinolates and changes in quality-related physiochemical characteristics of Guizhou suancai during the fermentation process - Hongmei Di; Jie Ma; Yi Zhang; Jia Wei; Jiao Yang; Jun Ma; Jinlin Bian; Jingyi Xu; Zhi Huang; Yi Tang; Huanxiu Li; Yangxia Zheng; et al. (Food Chemistry, 2023)

Anti-Vascular Endothelial Growth Factor Therapy Abolishes Glioma-Associated Endothelial Cell-Induced Tumor Invasion - Feng Tang; Feng-Ping Li; Xue-Tao Huang; Guo-Hua Wang; Ze-Fen Wang; Zhi-Qiang Li (Journal of Molecular Neuroscience, 2023)

Associations of exposure to multiple metals with the risk of age-related cataract in Anhui, China: a case–control study - Yan-Qing Li; Qian Wang; Ran Liu; Guo-Ao Li; Jia-Liu He; Fen Huang; Yan-Feng Zhou (Environmental Science and Pollution Research, 2023)

Association of exposure to multiple serum metals with the risk of chronic kidney disease in the elderly: a population-based case–control study - Wenlei Hu; Guoao Li; Jialiu He; Huanhuan Zhao; Hanshuang Zhang; Huanhuan Lu; Jianjun Liu; Fen Huang (Environmental Science and Pollution Research, 2022)

Short-term exposure to six air pollutants and cause-specific cardiovascular mortality of nine counties or districts in Anhui Province, China - Guoao Li; Huanhuan Zhao; Mingjun Hu; Jialiu He; Wanjun Yang; Hanshuang Zhang; Zhenyu Zhu; Jinliang Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Outdoor air pollution enhanced the association between indoor air pollution exposure and hypertension in rural areas of eastern China - Guoao Li; Huanhuan Lu; Wenlei Hu; Jianjun Liu; Mingjun Hu; Jialiu He; Fen Huang (Environmental Science and Pollution Research, 2022)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

The effects of air pollution on the lung cancer mortality in rural areas of eastern China: a multi-region study - Zhenqiu Zha; Guoao Li; Yili Lv; Lingli Liu; Jialiu He; Wei Xu; Dan Dai; Zhirong Liu; Fen Huang (Environmental Science and Pollution Research, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Effects of carbon dioxide and green space on sleep quality of the elderly in rural areas of Anhui Province, China - Guoao Li; Zhenyu Zhu; Mingjun Hu; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2022)

Six air pollutants and cause-specific mortality: a multi-area study in nine counties or districts of Anhui Province, China - Guoao Li; Huabing Wu; Qi Zhong; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Zhenyu Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Exposure to 2,4-dichlorophenol, 2,4,6-trichlorophenol, pentachlorophenol and risk of thyroid cancer: a case-control study in China - Wan-Jun Yang; Hua-Bing Wu; Chi Zhang; Qi Zhong; Ming-Jun Hu; Jia-Liu He; Guo-Ao Li; Zhen-Yu Zhu; Jin-Liang Zhu; Huan-Huan Zhao; Han-Shuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2021)

Associations between essential microelements exposure and the aggressive clinicopathologic characteristics of papillary thyroid cancer - Ming-Jun Hu; Jia-Liu He; Xin-Ran Tong; Wan-Jun Yang; Huan-Huan Zhao; Guo-Ao Li; Fen Huang (BioMetals, 2021)

Efficient propagation with in vitro seed germination of Vanda falcata - Xiao-fen Liu; Li-li Xiang; Yan Huang; Ya-jing Li; Fang Li (Journal of Zhejiang University-SCIENCE B, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Ginsenosides in root exudates of Panax notoginseng drive the change of soil microbiota through carbon source different utilization - Li-Fen Luo; Lei Yang; Zheng-Xu Yan; Bing-Bing Jiang; Su Li; Hui-Chuan Huang; Yi-Xiang Liu; Shu-Sheng Zhu; Min Yang (Plant and Soil, 2020)

Effect of the Interaction Between Cadmium Exposure and CLOCK Gene Polymorphisms on Thyroid Cancer: a Case-Control Study in China - Qian Zhang; Chunxiao Jiang; Haibo Li; Chi Zhang; Huabing Wu; Fen Huang (Biological Trace Element Research, 2020)

Dialectical behavior therapy-based psychological intervention for woman in late pregnancy and early postpartum suffering from COVID-19: a case report - Jin-wen Huang; Xiao-yi Zhou; Shao-jia Lu; Yi Xu; Jian-bo Hu; Man-li Huang; Hua-fen Wang; Chan-chan Hu; Shu-guang Li; Jing-kai Chen; Zhong Wang; Shao-hua Hu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Characterization of the complete chloroplast genome of Euryodendron excelsum (Pentaphylacaceae), a critically endangered species endemic to China - Xiang-gang Shi; Wei-xi Li; Fen Xing; Yu-bin Zhou; Wu-xia Guo; Ye-lin Huang (Conservation Genetics Resources, 2019)

Effect of Biochar on Growth, Photosynthetic Characteristics and Nutrient Distribution in Sugarcane - Fen Liao; Liu Yang; Qiang Li; Jianjun Xue; Yangrui Li; Dongliang Huang; Litao Yang (Sugar Tech, 2019)

Oral administration of Lactobacillus rhamnosus GG to newborn piglets augments gut barrier function in pre-weaning piglets - Yang Wang; Li Gong; Yan-ping Wu; Zhi-wen Cui; Yong-qiang Wang; Yi Huang; Xiao-ping Zhang; Wei-fen Li (Journal of Zhejiang University-SCIENCE B, 2019)

Genetic diversity and large-scale connectivity of the scleractinian coral Porites lutea in the South China Sea - Wen Huang; Ming Li; Kefu Yu; Yinghui Wang; Jingjing Li; Jiayuan Liang; Yanqiu Luo; Xueyong Huang; Zhenjun Qin; Guanghua Wang; Hongfei Su; Fen Wei (Coral Reefs, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Optimization of the culture medium for recombinant protein production under the control of the αAmy3 promoter in a rice suspension-cultured cell expression system - Yu-Kuo Liu; Chia-Wei Lu; Jer-Yuan Chang; Ching-Fan Lu; Chia-Chun Tan; Li-Fen Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Minimally Toxic Dose of Lipopolysaccharide and α-Synuclein Oligomer Elicit Synergistic Dopaminergic Neurodegeneration: Role and Mechanism of Microglial NOX2 Activation - Wei Zhang; Jun-hua Gao; Zhao-fen Yan; Xi-yan Huang; Peng Guo; Li Sun; Zhuo Liu; Yang Hu; Li-jun Zuo; Shu-yang Yu; Chen-Jie Cao; Xiao-min Wang; et al. (Molecular Neurobiology, 2018)

Two new biphenyls from the stems of Garcinia tetralata - Bing-Kun Ji; Xue-Mei Gao; Di Cui; Shan-Shan Wang; Wen-Zhong Huang; Yin-Ke Li; Shuang-Xi Mei; Zhi Yang; Gan-Peng Li; Meng-Yuan Jiang; Yong-Hui He; Zhi-Yong Jiang; et al. (Natural Product Research, 2017)

Strain distribution, growth eccentricity, and tension wood distribution in the plagiotropic and orthotropic branches of Koelreuteria henryi Dummer - Li-Fen Hung; Ching-Chu Tsai; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2017)

Effects of soybean isoflavone on intestinal antioxidant capacity and cytokines in young piglets fed oxidized fish oil - Lin Huang; Xian-yong Ma; Zong-yong Jiang; You-jun Hu; Chun-tian Zheng; Xue-fen Yang; Li Wang; Kai-guo Gao (Journal of Zhejiang University-SCIENCE B, 2016)

Study of tension wood in the artificially inclined seedlings of Koelreuteria henryi Dummer and its biomechanical function of negative gravitropism - Li-Fen Hung; Ching-Chu Tsai; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2016)

Hepatitis E virus infection activates signal regulator protein α to down-regulate type I interferon - Fen Huang; Chenchen Yang; Wenhai Yu; Yanhong Bi; Feiyan Long; Jue Wang; Yunlong Li; Shenrong Jing (Immunologic Research, 2016)

Separation and identification of a novel tadalafil analogue adulterant in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Ying Li; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

A single-repeat MYB transcription repressor, MYBH, participates in regulation of leaf senescence in Arabidopsis - Chun-Kai Huang; Pei-Ching Lo; Li-Fen Huang; Shaw-Jye Wu; Ching-Hui Yeh; Chung-An Lu (Plant Molecular Biology, 2015)

Biochar Improves Sugarcane Seedling Root and Soil Properties Under a Pot Experiment - Liu Yang; Fen Liao; Min Huang; Litao Yang; Yangrui Li (Sugar Tech, 2015)

Effect of Trash Addition to the Soil on Microbial Communities and Physico-Chemical Properties of Soils and Growth of Sugarcane Plants - Qing Liao; Guang-Po Wei; Gui-Fen Chen; Bin Liu; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2014)

Risk for estrogen-dependent diseases in relation to phthalate exposure and polymorphisms of CYP17A1 and estrogen receptor genes - Po-Chin Huang; Wan-Fen Li; Pao-Chi Liao; Chien-Wen Sun; Eing-Mei Tsai; Shu-Li Wang (Environmental Science and Pollution Research, 2014)

The expression profile and promoter analysis of β-N-acetylglucosaminidases in the silkworm Bombyx mori - Yuan-fen Zhai; Ming-xia Huang; Yu Wu; Guo-dong Zhao; Jie Du; Bing Li; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Divergence of the expression and subcellular localization of CCR4-associated factor 1 (CAF1) deadenylase proteins in Oryza sativa - Wei-Lun Chou; Li-Fen Huang; Jhen-Cheng Fang; Ching-Hui Yeh; Chwan-Yang Hong; Shaw-Jye Wu; Chung-An Lu (Plant Molecular Biology, 2014)

Role and Mechanism of Microglial Activation in Iron-Induced Selective and Progressive Dopaminergic Neurodegeneration - Wei Zhang; Zhao-fen Yan; Jun-hua Gao; Li Sun; Xi-yan Huang; Zhuo Liu; Shu-yang Yu; Chen-Jie Cao; Li-jun Zuo; Ze-Jie Chen; Yang Hu; Fang Wang; et al. (Molecular Neurobiology, 2014)

Multi-mode PolInSAR experiments using an airborne X-band SAR system in China - Li-Jun Lu; Ji-Xian Zhang; Fen-Fen Hua; Guo-Man Huang (International Journal of Remote Sensing, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Improvement of fluorescent chromosome in situ PCR and its application in the phylogeny of the genus Fagopyrum Mill. using nuclear genes of chloroplast origin (cpDNA) - Fen-Long Li; Friedrich J. Zeller; Kai-Feng Huang; Tao-Xiong Shi; Qing-Fu Chen (Plant Systematics and Evolution, 2013)

Uptake of arsenic species by turnip ( Brassica rapa L.) and lettuce ( Lactuca sativa L.) treated with roxarsone and its metabolites in chicken manure - Lian Xi Huang; Li Xian Yao; Zhao Huan He; Chang Min Zhou; Guo Liang Li; Bao Mei Yang; Ying Fen Li (Food Additives & Contaminants: Part A, 2013)

Sugar starvation- and GA-inducible calcium-dependent protein kinase 1 feedback regulates GA biosynthesis and activates a 14-3-3 protein to confer drought tolerance in rice seedlings - Shin-Lon Ho; Li-Fen Huang; Chung-An Lu; Siou-Luan He; Chun-Chin Wang; Sheng-Ping Yu; Jychian Chen; Su-May Yu (Plant Molecular Biology, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Biomechanical features of eccentric cambial growth and reaction wood formation in broadleaf tree branches - Ching-Chu Tsai; Li-Fen Hung; Ching-Te Chien; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2012)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

Synthesis, properties and application research of atrazine Fe3O4@SiO2 magnetic molecularly imprinted polymer - Hai-Fen Men; Hai-Qing Liu; Zu-Lei Zhang; Jing Huang; Jian Zhang; Yun-Yun Zhai; Lei Li (Environmental Science and Pollution Research, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Seasonal variation in population characteristics and management implications for brown rats (Rattus norvegicus) within their native range in Harbin, China - Da-Wei Wang; Lin Cong; Ling-Fen Yue; Bao-Huan Huang; Jian-Xu Zhang; Yu Wang; Ning Li; Xiao-Hui Liu (Journal of Pest Science, 2011)

HLA polymorphism of the Zhuang population reflects the common HLA characteristics among Zhuang-Dong language-speaking populations - Li Shi; Xiao-qin Huang; Lei Shi; Yu-fen Tao; Yu-feng Yao; Liang Yu; Ke-qin Lin; Wen Yi; Hao Sun; Katsushi Tokunaga; Jia-you Chu (Journal of Zhejiang University-SCIENCE B, 2011)

Biomechanical modeling of gravitropic response of branches: roles of asymmetric periphery growth strain versus self-weight bending effect - Yan-San Huang; Li-Fen Hung; Ling-Long Kuo-Huang (Trees, 2010)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

Effects of the multiple polyadenylation signal AAUAAA on mRNA 3′-end formation and gene expression - Hsin-Hung Lin; Li-Fen Huang; Hsiao-Chien Su; Shih-Tong Jeng (Planta, 2009)

Flood hazard in Hunan province of China: an economic loss analysis - Xin Huang; Hongzhuan Tan; Jia Zhou; Tubao Yang; Abuaku Benjamin; Shi Wu Wen; Shuoqi Li; Aizhong Liu; Xinhua Li; Shuidong Fen; Xinli Li (Natural Hazards, 2008)

Receptor-mediated gene delivery using polyethylenimine (PEI) coupled with polypeptides targeting FGF receptors on cells surface - Da Li; Qing-qing Wang; Gu-ping Tang; Hong-liang Huang; Fen-ping Shen; Jing-zhong Li; Hai Yu (Journal of Zhejiang University-SCIENCE B, 2006)

Synthesis of Site-Specifically Dimethylated and Trimethylated Peptides Derived from Histone H3 N-Terminal Tail - Zhi-Ping Huang; Jin-Tang Du; Yu-Fen Zhao; Yan-Mei Li (International Journal of Peptide Research and Therapeutics, 2006)

Functional analysis of helicase and three tandem HRDC domains of RecQ in Deinococcus radiodurans - Li-fen Huang; Xiao-ting Hua; Hui-ming LU; Guan-jun Gao; Bing Tian; Bing-hui Shen; Yue-jin Hua (Journal of Zhejiang University-SCIENCE B, 2006)

Production of human serum albumin by sugar starvation induced promoter and rice cell culture - Li-Fen Huang; Yu-Kuo Liu; Chung-An Lu; Shie-Liang Hsieh; Su-May Yu (Transgenic Research, 2005)

The Elp3 subunit of human Elongator complex is functionally similar to its counterpart in yeast - Fen Li; Jun Lu; Qiuju Han; Guoping Zhang; Baiqu Huang (Molecular Genetics and Genomics, 2005)